OsSPL9 Regulates Grain Number and Grain Yield in Rice - Hu, Li; Chen, Weilan; Yang, Wen; Li, Xiaoling; Zhang, Cheng; Zhang, Xiaoyu; Zheng, Ling; Zhu, Xiaobo; Yin, Junjie; Qin, Peng; Wang, Yuping; Ma, Bingtian; et al. (Frontiers in Plant Science, 2021)
Rice grain yield consists of several key components, including tiller number, grain number per panicle (GNP) and grain weight. Among them, GNP is mainly determined by panicle branches and spikelet formation. Here, we identified a gene affecting GNP, OsSPL9, which encodes an SQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) family protein. The mutation of OsSPL9 significantly reduced secondary branches and GNP. OsSPL9 was highly expressed in the early developing young panicles, consistent with its function in regulating panicle development. By combining expression analysis and dual-luciferase assays, we further confirmed that OsSPL9 directly activates the expression of RCN1 (rice TERMINAL FLOWER 1/CENTRORADIALIS homolog) in the early developing young panicle to regulate the panicle branches and GNP. Haplotype analysis showed that Hap3 and Hap4 of OsSPL9 might be favorable haplotypes contributing to high GNP in rice. These results provide new insights on high grain number breeding in rice.